PENGARUH SERVICESCAPE DAN VARIASI PRODUK TERHADAP MINAT BELI PADA GONG RESTORAN JATILUWIH - Ni Putu Wiwik Nia Utari; I Gusti Ngurah Agung Gede Eka Teja Kusuma; I Wayan Gede Antok Setiawan Jodi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Buying interest is closely related to consumer purchasing decisions, interest is used to predict a person's tendency to do or not do buying behavior. The purpose of the study was to determine the effect of servicescape and product variations on buying interest. The object of this research is the influence of Servicespace and Product Variations on Buying Interest at Gong Restaurant Jatiluwih. The number of respondents in this study were 85 people. Methods of data collection using a questionnaire. Data analysis used multiple linear regression. The result of this research is that servicescape has a positive and significant effect on buying interest at Gong Restaurant Jatiluwih. This shows that the better the servicescape of Gong Restaurant Jatiluwih, the higher the buying interest in the product. Product variations have a positive and significant effect on buying interest at Gong Restaurant Jatiluwih. This shows that the better the variety of Gong Restoran Jatiluwih products, the higher the buying interest in these products.